2022
DOI: 10.3390/jcm11020291
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Existing Hypertension Is Related with Disproportions in T-Lymphocytes in Older Age

Abstract: Age-related immune deficiencies increase the risk of comorbidities and mortality. This study evaluated immunosenescence patterns by flow cytometry of naïve and memory T cell subpopulations and the immune risk profile (IRP), expressed as the CD4/CD8 ratio and IgG CMV related to comorbidities. The disproportions in naïve and memory T cells, as well as in the CD4/CD8 ratio, were analysed in 99 elderly individuals (71.9 ± 5.8 years) diagnosed with hypertension (n = 51) or without hypertension (n = 48), using an ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…We observed that patients aged ≥ 63 years (cut-off value) with NRL ≥ 4.56 × 10 3 /µL ran a significantly higher risk of shorter overall survival time. One of the features of immunoageing is a chronic and systemic low-grade inflammation [ 29 ]. The inflammation that often accompanies the elderly is also associated with the development of all stages of tumours, both transformation and metastasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed that patients aged ≥ 63 years (cut-off value) with NRL ≥ 4.56 × 10 3 /µL ran a significantly higher risk of shorter overall survival time. One of the features of immunoageing is a chronic and systemic low-grade inflammation [ 29 ]. The inflammation that often accompanies the elderly is also associated with the development of all stages of tumours, both transformation and metastasis [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally complicated by the simultaneous course of oxidative stress and inflammation in the senescence of vascular endothelial cells [ 3 ]. The risk factors of enhanced aging, such as low physical activity level and high visceral fat content, can induce alterations in endothelium morphology and metabolism, which contributes to arterial stiffness, atherosclerosis, hypertension, stroke, and coronary artery disease in older adults [ 14 , 24 ]. In this regard, aging is a major risk factor and represents a major global health challenge in the pathogenesis of CVDs [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of CD4 + naïve T lymphocytes is stable for most of the lifespan, but it markedly declines at the age of 70 years. Contrastingly, CD8 + naïve T lymphocytes appear to be more susceptible to apoptosis and thus more sensitive to age-related changes [ 14 ]. The immunosenescence-related disproportion in T lymphocytes may have important consequences for endothelial dysfunction, which is a key event in vascular aging leading to the initiation, progress, and advancement of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations